The Influence of Organizational Culture and Motivation on Work Discipline - Rakhman, Arif; Sungkono; Rieke Retnosary (Research in Management of Technology and Business, 2026)
Based on research, The authors aimed to determine how the influence of Organizational Culture and Motivation on Work Discipline. Descriptive and verification approaches were used in this study. A total of 92 employees of PT EXSPRESSINDO 88 NUSANTARA became the research sample, and the authors used quantitative research methodology. Path analysis has used this study. Use of SPSS 26 software as a research tool. The findings show a moderately significant correlation (0.458) between corporate culture and motivation. Work discipline is significantly influenced by corporate culture, as seen from the tcount of 6.558 > 1.661. Work discipline is significantly influenced by motivation, as seen from the tcount of 6.606 > 1.661. Work discipline is significantly influenced by organizational culture and motivation simultaneously, with a sig value of 0.000 < 0.005. Path Analysis findings show that organizational culture factors have an impact of = 0.000, motivation = 0.002, and incentives = 0.000 < 0.005